2004
DOI: 10.1038/sj.gene.6364123
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in multidrug resistance 1 (MDR1) gene are associated with refractory Crohn disease and ulcerative colitis

Abstract: We used coding and noncoding polymorphisms evenly spaced across the ABCB1/MDR1 gene to perform association analysis in Slovenian patients with inflammatory bowel diseases and to obtain haplotype structure and patterns of linkage disequilibrium (LD) in the MDR1 gene. A disease association study was performed in 307 IBD patients, including 144 patients with ulcerative colitis (UC) and 163 patients with Crohn's disease (CD), and 355 healthy controls. Here we report an association between MDR1 alleles, polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
121
5
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 33 publications
15
121
5
6
Order By: Relevance
“…A slight, but statistically insignificantly increased value of 54% in the mutant allele T was only seen in patients with UC (OR: 1.76, CI: 0.30 -9.78, p< 0.46). Glas et al [47] and Potocnik et al [24] have reported similar ratios. …”
Section: Mdr1 C3435tsupporting
confidence: 58%
See 1 more Smart Citation
“…A slight, but statistically insignificantly increased value of 54% in the mutant allele T was only seen in patients with UC (OR: 1.76, CI: 0.30 -9.78, p< 0.46). Glas et al [47] and Potocnik et al [24] have reported similar ratios. …”
Section: Mdr1 C3435tsupporting
confidence: 58%
“…MDR1 G2677A is not equally well understood as its prevalence is very low (around 1%) [12] and high sample sizes are needed to give valid estimates. Some authors therefore chose to exclude it in their studies [23,24].…”
Section: P-glycoprotein (P-gp Mdr1)mentioning
confidence: 99%
“…In another study, haplotype 1236T/2677G/3435T carriers demonstrated higher P-gp activity when compared to non-carriers [14]. The 1236T/2677T/3435T haplotype was also shown to be associated with a slightly greater risk of developing refractory Crohn's disease (P=0.044) [26]. The same study showed that when each SNP occurred separately, there was no significant correlation with the development of the disease.…”
Section: Introductionmentioning
confidence: 59%
“…Present approaches have not been able to discern whether these other genes or the class Ⅱ genes are the true risk genes in the HLA locus. [79][80][81][82] , multiple polymorphisms in the MDR1/ABCB1 gene on chromosome 7q [83][84][85][86][87][88][89][90][91][92] , and polymorphisms in the DLG5 gene on chromosome 10q [70,[93][94][95][96][97][98][99][100][101][102] . (See section C.4.1.)…”
Section: Hla Associationsmentioning
confidence: 99%